Analyzing Communication Strategies in Polyglot Indonesia National Gathering Chapter Semarang: Ethnography of Communication Study - Zakiyah, Nur Hanifatul (Indonesian Journal of Multidisciplinary Science, 2023)
This article presents the results of an ethnographic research on communication about the Indonesian Polyglot community, with a focus on the Semarang Chapter of the Indonesian Polyglot. Communication ethnography is used as an approach to understand the communication practices that occur in this community. This study involved an interview method with members of the Semarang Chapter of the Indonesian Polyglot as the main informant. The data collected was then analyzed using the Ethnographic Communication theory framework developed by Dell Hymes. This data analysis includes the communication practices, norms, and values found within this polyglot community. The results of the study show that communication within the Polyglot Indonesia Chapter Semarang community is very dynamic and is influenced by the diversity of languages owned by the members. Community members use various languages in their interactions, such as Indonesian, foreign languages, and regional languages. They also use effective communication strategies, such as code-switching, code-mixing, and body language, to facilitate understanding and successful communication. This study has important significance in the context of the study of cross-cultural and multilingual communication. In this era of globalization, cross-cultural communication is becoming increasingly relevant, and the study of polyglot communities can provide valuable insights into understanding how people communicate in multilingual and multicultural situations. The results of this research can also provide valuable input for the development of the Indonesian Polyglot community and similar communities in Indonesia.